Centrifuge modelling for seismic retrofit design of an immersed tube tunnel. Issue 2 (June 2003) - Adalier, K.; Abdoun, T.; Dobry, R.; Phillips, R.; Yang, D.; Naesgaard, E.
Abstract : A centrifuge testing program was conducted to assess the earthquake performance of countermeasure retrofit techniques for an existing concrete tunnel embedded in a liquefiable sandy deposit. In a series of three separate heavily instrumented model tests, a tunnel section-foundation system was studied first without retrofitting, and then with a densified-wall and a gravel-wall liquefaction countermeasure techniques. The test results provided valuable insights into the underlying mechanism and effectiveness of each countermeasure and served as basis for calibration and validation of computational modelling of the George Massey Tunnel seismic retrofit design. Test results showed that the implemented countermeasures significantly reduced the tunnel movements. The gravel-wall technique was found to be particularly effective in reducing the extent of liquefaction as well as reinforcing the tunnel-foundation system against earthquake induced deformations. The centrifuge test results and the calibrated numerical model studies led to a final ground improvement scheme that included both stone column densification and seismic gravel drains.